Assessment of Patient’s Satisfaction and Associated Factors regarding Postoperative Pain Management at the University of Gondar Compressive Specialized Hospital, Northwest Ethiopia - Yosef Belay Bizuneh; Girmay Fitiwi Lema; Demeke Yilkal Fentie; Yophtahe Woldegerima Berhe; Henos Enyew Ashagrie (Pain Research and Management)
Objective. We aimed to assess the level of patient’s satisfaction and associated factors regarding postoperative pain management. Methods. An institution-based cross-sectional study was conducted from April to May 2018 at the University of Gondar, and comprehensive specialized hospital data were collected through semistructured questionnaire and chart review. Level of satisfaction was measured using five-point Likert scale. Statistical analysis was done using SPSS software version 23. Both bivariable and multivariable logistic regression analyses were done. Variables of P value ≤0.2 in the bivariable analysis were a candidate for multivariable logistic regression. A P value ≤0.05 was considered as significantly associated with patient’s level of satisfaction at 95% CI. Results. A total of 418 patients were included in this study with a response rate of 98.58%. The overall proportion of patients who were satisfied with pain management services was 72.2% (95% CI: 67.7–76.6). ASA1 (AOR = 3.55: 95% CI = 1.20–10.55) and ASA2 patients (AOR = 3.72: 95% CI = 1.04–13.28), absence of postoperative pain (AOR = 1.86: 95% CI = 1.02–3.39), peripheral nerve block done (AOR = 9.14: 95% CI = 3.93 20.86), received analgesic before request (AOR = 6.90: 95% CI = 3.72–12.83), and received systemic analgesics (AOR = 6.10: 95% CI = 1.17–33.91) were significantly associated with the level of satisfaction. Conclusion. The level of patient satisfaction with postoperative pain management was considerably low. Hence, it is vital to implement time-interval pain assessment method during the first 24 hours of postoperative period and treat accordingly based on the WHO pain ladder. Moreover, we suggested that all patients who underwent major surgery should receive peripheral nerve block as part of multimodal analgesia to decrease the incidence and severity of post op pain.